Discovery Learning and Modeling in Teaching Tennis Skills - Kalapoda, Ευπραξία; Michalopoulou, Μαρία; Betichavas, Άγγελος; Ageloussis, Νίκος; Taxildaris, Κυριάκος (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to determine the effect of different teaching methods on learning a novel motor skill. Seventy two subjects (M = 8.5, SD= 1 year) were randomly assigned to four groups. Subjects in group A (expert model group) monitored an expert’s athlete perform and received verbal instructions as a feedback. Subjects in group B (learning model group), monitored a learning model’s trials and received verbal instructions as a feedback. Subjects in group C (discovery learning group) received verbal instructions and did not received any feedback during their practice sessions. Subjects in group D (control group) received augmented feedback with verbal instructions, during their practice sessions from the instructor. Subjects participated in 12 practice sessions. Univariate ANOVA’s with repeated measures on the first factor (3 measures x 4 methods), when performance scores received, revealed a significant measure by method interaction (p< .05). Expert model group scored higher on the acquisition and retention test than on pre-test (p<.05). Learning model group scored higher on the acquisition and retention test than on pre-test (p< .05). Discovery learning group had higher performance scores on the retention test than on pre-test (p< .05). Control group had higher performance scores on the retention test than on pre-test (p< .05). When outcome scores received, revealed no significant measure by method interaction (p> .05). However, when outcome and performance scores received, there were revealed significant effects between measures (p< .05) and (p< .05). Discovery learning group revealed significant learning effects after the retention interval, a time that can be used by the young learner to process information and search on his own for solutions to his motor problems. These results suggest that all four methods had significant contribution in learning a complex motor skill and the teaching method that would maximize the learning effects depends on the characteristics of the motor task and learning environment.